The radiation resistance of human multipotent mesenchymal stromal cells is independent of their tissue of origin - Rühle, Alexander; Xia, Oliver; Trinh, Thuy; Richter, Wiltrud; Wuchter, Patrick; Debus, Jürgen; Saffrich, Rainer; Huber, Peter E.; Nicolay, Nils (International journal of radiation oncology, biology, physics, 2018)
Purpose - Human mesenchymal stromal cells (MSCs) may aid the regeneration of ionizing radiation (IR)-induced tissue damage. They can be harvested from different tissues for clinical purposes; however, the role of the tissue source on the radiation response of human MSCs remains unknown. - Methods and Materials - Human MSCs were isolated from adipose tissue, bone marrow, and umbilical cord, and cellular survival, proliferation, and apoptosis were measured after irradiation. The influence of IR on the defining functions of MSCs was assessed, and cell morphology, surface marker expression, and the differentiation potential were examined. Western blot analyses were performed to assess the activation of DNA damage signaling and repair pathways. - Results - MSCs from adipose tissue, bone marrow, and umbilical cord exhibited a relative radioresistance independent of their tissue of origin. Defining properties including cellular adhesion and surface marker expression were preserved, and irradiated MSCs maintained their potential for multilineage differentiation irrespective of their tissue source. Analysis of activated DNA damage recognition and repair pathways demonstrated an efficient repair of IR-induced DNA double-strand breaks in MSCs from different tissues, thereby influencing the induction of apoptosis. - Conclusions - These data show for the first time that MSCs are resistant to IR and largely preserve their defining functions after irradiation irrespective of their tissue of origin. Efficient repair of IR-induced DNA double-strand breaks and consecutive reduction of apoptosis induction may contribute to the tissue-independent radiation resistance of MSCs.
Gesehen am 26.04.2019